Perinatal anxiety and depression amidst the COVID-19 pandemic in Dubai, United Arab EmiratesAJOG Global Reports at a Glance - Zenab Yusuf Tambawala, MS, MRCOG; Shabnam Saquib, MD, FRCOG; Ayesha Salman, MRCOG; Munia Khalid, MBBS; Hiyam Beshtawi, MBBS; Elham Ali Akbari, MBBS; Amina Binashoor, MBBS; Nawal Hubaishi, MRCOG; Lama Khalid Hamza, MD; Maryam Al Rayssi, MRCOG (Elsevier, 2023)
BACKGROUND: Pregnancy and COVID-19 increase the risk of mental health conditions. The stress of pregnancy, childbirth, and uncertainty about the global pandemic has negatively affected the obstetrical population. OBJECTIVE: This study aimed to investigate the effects of the COVID-19 pandemic in terms of anxiety and depression in antenatal and postnatal mothers. STUDY DESIGN: This was a cross-sectional observational study conducted at Dubai Hospital, United Arab Emirates, evaluating depression and anxiety (point prevalence) with the Edinburgh Postnatal Depression Scale and Generalized Anxiety Disorder-7 scale. RESULTS: Of the 784 women approached, 438 consented to participate in our survey; 43.6% of the women screened positive for depression by the Edinburgh Postnatal Depression Scale (with a cutoff score ≥10), and 42% had a Generalized Anxiety Disorder-7 score of ≥5, indicating anxiety. Both anxiety and depression were found in 32.4% of the women; 7.5% had considered self-harm in the last 14 days, and 15% had COVID-19 during the current pregnancy. The 11.87% who had COVID-19, but before the pregnancy, had higher mean Edinburgh Postnatal Depression Scale and Generalized Anxiety Disorder-7 scores than others. Surprisingly, the women who had COVID-19 during pregnancy had statistically significantly (P<.05) lower Edinburgh Postnatal Depression Scale and Generalized Anxiety Disorder-7 scores. University graduates had significantly (P<.05) higher Edinburgh Postnatal Depression Scale and Generalized Anxiety Disorder-7 scores. Women of Middle Eastern ethnicity (50% positive for depression and 48.5% for anxiety) were more prone to depression and anxiety compared with South Asian (29% positive for depression and 25.2% for anxiety) and African women (39.6% positive for depression and 43.4% for anxiety). There was no statistically significant difference between antenatal and postnatal patients in the prevalence of anxiety or depression. CONCLUSION: The COVID-19 pandemic is associated with an increase in depression and anxiety in pregnant and postnatal women. Women who were more concerned about the effects of the pandemic had higher mean Edinburgh Postnatal Depression Scale and Generalized Anxiety Disorder-7 scores. Additional psychological support for women is necessary during the pandemic for maternal perinatal well-being.